Răspuns :
a² - b² = (a + b)(a - b)
a² - b² = 2003
(a + b)·(a - b) = 2003·1 =>
{ a + b = 2003
{ a - b = 1
_____________ +
2a = 2003 + 12a = 2004
a = 2004 : 2
a = 1002 [PRIMUL NR]
b = 2003 - 1002
b = 1001 [AL DOILEA NR] 1
002² - 1001² = 2003
a² - b² = 2003
(a + b)·(a - b) = 2003·1 =>
{ a + b = 2003
{ a - b = 1
_____________ +
2a = 2003 + 12a = 2004
a = 2004 : 2
a = 1002 [PRIMUL NR]
b = 2003 - 1002
b = 1001 [AL DOILEA NR] 1
002² - 1001² = 2003
Am atasat rezolvarea ex 1 , cum nu ai mentionat suma de cate numere sa fie am doua variante atasate Spor